Water-in-Silicone Emulsion – The Approach to an Ideal BB Cream - Huynh, Nhu Thao; Cuong, Quoc Nguyen; Tran, Thanh Men; Nguyen, Tuan Trong; Bui, Thi Buu Hue; Tran, Quang De (Indian Journal of Pharmaceutical Education and Research, 2022)
Silicone is a widely-used cosmetic ingredient, whose advantages are perceived as detackification, soft and non-greasy feeling, and excellent spreading quality. Therefore, in this work, we aim to formulate BB cream based on W/Si emulsion to make the most out of these benefits. Two different emulsifiers namely PEG/PPG-18/18 Dimethicone – a common silicone emulsifier and Lauryl PEG-10 Tris(Trimethylsiloxy)silylethyl Dimethicone – a new silicone emulsifier, were tested. Upon completion, the properties and stabilities of two samples were investigated to compare their emulsifying ability. At the concentration of 3%, BB Cream made from Lauryl PEG-10 Tris(Trimethylsiloxy) silylethyl Dimethicone appears to be more stable compared to its counterpart, which was proven explicitly by physical appearance, viscosity, and microscopic observation in our study. Our formulated BB Cream was successfully undergone stability tests, then proceeded to a sensory evaluation in comparison with a commercial BB Cream. With good properties testifying for Lauryl PEG-10 Tris(Trimethylsiloxy)silylethyl Dimethicone from our studies, the developed composition is expected to represent a real asset in future make-up formulations.
Keywords: Silicone; BB Cream; W/Si emulsion; Dimethiconol; Lauryl PEG-10; Tris(Trimethylsiloxy)silylethyl Dimethicone